BEHAVIORAL MODELING OF SMITH-WATERMAN ALGORITHM FOR DNA COMPARISONUSING FPGA - Swaroopa S. Kulkarni; Digamber B.Gote (International Journal of Innovations in Engineering Research and Technology, 2021)
Smith Waterman algorithm uses divide and conquer approach. Forfinding the difference between two DNA strands. For implementation of this algorithm previously structural modeling was started and continued till the configuration of the basic cell the matrix structure. But it was found after creating its schematic symbol that the behavioral modeling would be more simple and convenient for this work. In this paper the implementation is discussed usingbehavioral modeling for Spartan-6 family of FPGA in order to implement the Smith –Waterman algorithm.